A brief history of small business in Australia, 1970-2010. Issue 2 (14th October 2014) - T. Schaper, Michael
Abstract : Purpose: – The purpose of this paper is to provide an overview of the development of the SME sector in Australia, concentrating on a number of key areas: small business definitions and numbers; the role of government; the emergence of key industry groups; and the evolution of education, training and research services. Design/methodology/approach: – The study is a result of extensive literature reviews, desk research and the recollections of various participants in the field. Findings: – There have been major changes to the Australian small business sector over the last 40 years. In 1983-1984 there were an estimated 550, 000 small firms, and by 2010 this had grown to almost two million. Government involvement in, and support for, SMEs was virtually non-existent before 1970. Following the delivery of the Wiltshire report (1971), however, both state and federal governments responded by developing specialist advisory services, funding programmes and other support tools. Virtually non-existent before the 1970s, several peak industry associations were formed between 1977 and the 1990s. At the same time, formal education and teaching in the area expanded in the 1970s and 1980s and is now widespread. Practical implications: – Development of the small business sector in Australia has often paralleled similar trends in other OECD nations. State and territory governments have often (but not always) been the principal drivers of policy change. Originality/value: – There has been no little, if any, prior documentation of the evolution of the small business sector in Australia in the last 40 years.